Building Regional Readiness Indonesia’s Leadership in Enhancing AHA Centre’s Disaster Response Capabilities - Rahmadhani, Putri; Perwita, Anak Agung Banyu; Ramsi, Oktaheroe (International Journal of Humanities, Education, and Social Sciences, 2025)
Indonesia, one of the most disaster-prone countries in the world, plays a strategic role in advancing regional disaster preparedness through its leadership in the ASEAN Coordinating Centre for Humanitarian Assistance on Disaster Management (AHA Centre). This study examines Indonesia’s leadership in the AHA Centre by employing the theoretical frameworks of Security Community (Karl Deutsch) and Norm Life Cycle (Finnemore & Sikkink) to analyze how Indonesia promotes cooperative norms and fosters a collective regional identity in disaster management. Utilizing a qualitative approach, the study evaluates Indonesia’s contributions in policy harmonization, operational readiness, resource mobilization, and norm internalization across ASEAN member states. The findings indicate that Indonesia functions as a norm entrepreneur by leading initiatives such as joint training programs, simulation exercises, information-sharing mechanisms, and the development of early warning systems—efforts that significantly enhance regional resilience and inter-state collaboration. Nonetheless, the study also identifies key challenges, including disparities in national disaster management capacities, inconsistent political commitment, and technological integration gaps, which impede the full realization of a cohesive regional response. The study concludes that Indonesia’s leadership has been instrumental in strengthening both national and regional disaster management frameworks and advancing ASEAN’s vision of a resilient community. Sustained efforts in policy alignment, capacity building, and resource sustainability are essential for deepening ASEAN’s collective disaster preparedness and response mechanisms.